Feasibility and Reliability of Two-Dimensional Shear-Wave Elastography of the Liver of Clinically Healthy Cats - Kim, Kyeonga (Front Vet Sci, 2020)
Given the broad overlap of normal and abnormal liver tissue in the subjective evaluation of the liver in conventional B-mode ultrasonography, there is a need for a non-invasive and quantitative method for the diagnosis of liver disease. Novel two-dimensional shear-wave elastography (2-D SWE) can measure tissue stiffness by propagation of the shear wave induced using acoustic radiation force impulse in real time. To the best of our knowledge, two-dimensional shear-wave measurement of the liver in cats has not been reported to date. This study assessed the feasibility, reliability, normal values, and related influencing factors of 2-D SWE for assessment of the feline liver without anesthesia and breath-holding. Two-dimensional shear-wave ultrasonography was performed by two evaluators at the right and left sides of the liver. Twenty-nine client-owned clinically healthy adult cats were included. The means and standard deviations for the shear-wave speed and stiffness in the right liver were 1.52 ± 0.13 m/s and 6.94 ± 1.26 kPa, respectively, and those for the left liver were 1.61 ± 0.15 m/s and 7.90 ± 1.47 kPa, respectively. Shear-wave speed (P = 0.005) and stiffness (P = 0.002) were significantly lower in the right liver when compared to the left. The intraclass correlation value for liver stiffness was 0.835 and 0.901 for the right and left liver, respectively, indicating high interobserver agreement. Age, weight, body condition score (BCS), gabapentin administration, and measurement depths were not significantly correlated with liver stiffness or elastography measurements (P > 0.05). Our findings suggest that 2-D SWE measurements of the liver are not influenced significantly by age, weight, or BCS and can be reliably performed without anesthesia and breath-holding in cats. The values determined here can help form the basis for reference elastography values for evaluation of the feline liver.